1991
DOI: 10.1577/1548-8667(1991)003<0168:daeoam>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Monoclonal-Antibody-Based Enzyme-Linked Immunosorbent Assay for the Diagnosis ofRenibacterium salmoninarumInfection

Abstract: A monoclonal-antibody-based enzyme-linked immunosorbent assay (ELISA) was developed for the diagnosis of bacterial kidney disease (BKD). This ELISA can detect Renibacterium salmoninarum antigen at concentrations as low as 0.05-0.1 Mg/mL. During the 1988-1989 spawning season, 60 coho salmon Oncorhynchus kisutch, 60 chinook salmon O. tshawytscha, and 60 steeihead O. mykiss (Great Lakes rainbow trout) were caught and screened for BKD with the developed ELISA and a direct fluorescent antibody technique (FAT). Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…However, other investigators have shown a similar lack of agreement of FAT results among laboratories (Armstrong et al 1989b), and FAT results also disagreed with ELISA results , Hsu et al 1991, Pascho et al 1991 and with results of other detection methods more sensitive than the FAT, but less so than the ELISA (Lee & Gordon 1987, Griffiths et al 1991, when 50 to 100 fields were examined. Consequently, examination of more than 30 fields by the FAT did not appear worthwhile in this study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, other investigators have shown a similar lack of agreement of FAT results among laboratories (Armstrong et al 1989b), and FAT results also disagreed with ELISA results , Hsu et al 1991, Pascho et al 1991 and with results of other detection methods more sensitive than the FAT, but less so than the ELISA (Lee & Gordon 1987, Griffiths et al 1991, when 50 to 100 fields were examined. Consequently, examination of more than 30 fields by the FAT did not appear worthwhile in this study.…”
Section: Discussionmentioning
confidence: 88%
“…Due to the ease of application, the most common method has been examination of kidney smears by the fluorescent antibody test (FAT) which replaced the less sensitive Gram stain (Bullock & Stuckey 1975, Bullock et al 1980). More recently, the enzyme-linked immunosorbent assay (ELISA) has been shown to be the most sensitive, accurate, quantitative, and easily automated test for large-scale detection of Rs soluble antigens in salmonids , Turaga et al 1987, Sakai et al 1989, Hsu et al 1991, Pascho et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, false-positive R. salmoninarum reactions have been reported with the ELISA (Dixon 1985, Turaga et al 1987. In attempts to avoid false-positive reactions, some workers have used monoclonal antibodies directed against selected epitopes of p57 (Wiens & Kaattari 1989, Hsu et al 1991, Rockey et al 1991. Others have used Western blot analysis to make the diagnosis less equivocal (Olivier et al 1992).…”
mentioning
confidence: 99%
“…For example, localized infections can occur in the head and skin tissues, which are sites not usually assayed in screening programs (29). Several ELISAs have been described utilizing either polyclonal antibodies (21,24,27,30), monoclonal antibodies (33), or a combination of both types of antibodies (23). Assays relying on polyclonal antisera are limited by reagent availability, lot consistency, and cross-reactivity (29).…”
Section: Discussionmentioning
confidence: 99%